LANGUAGE ACQUISITION AS A PROCESS OF HUMAN MIND - Kuchkarova Mushtariy (PEDAGOGS, 2024)
Annotation: The purpose of this article is to give information about how human brain develops when the person comes to life and look into some interesting details which human brain posses even in early period of the life. The author provides information about how and when the acquiring process begins and what peculiar facilities does the brain have, and also this paper includes data about how acquiring process occur in the mind, then how it comprehends the new information and in what ages does the brain start to produce the learned materials.